Carbon Electrode and Buleleng Seawater in Degrading the Leachate in Bengkala Village of Buleleng Regency by Using Electro-Oxidation Techniques - Wiratini, Ni Made; Lasia, I Ketut; Rakhman, Khusna Arif; Cipta, Indra (Universitas Jenderal Soedirman, 2026)
ABSTRACT. This research aims to study the effectiveness of using carbon electrodes and Buleleng seawater in degrading leachate through electro-oxidation techniques. Electro-oxidation is a waste processing technology that cannot be biologically degraded, has high efficiency and degradation speed, is easy to operate, has low cost, and is environmentally friendly. Leachate is taken from the dumping ground in Bengkala village of Buleleng Regency. The volume of leachate used was 50 mL. The influence of the surface area of the electrode, the distance between electrodes, voltage, contact time, and the amount of seawater were also studied. All treated leachates were then measured for COD, DO, absorbance, BOD, and pH. The results showed that Buleleng sea water contains chlorine ions 16.862 g/L. COD, DO, absorbance, BOD, and pH of leachate before electro-oxidation 38.763x103, 0, 17.1, 0, and 9 mg/L respectively. The surface area of the electrodes, the distance between electrodes, voltage, contact time, and the amount of seawater used were most effective in degrading leachate in 10.551 cm2, 3 cm, 13.5 volts, 1.5 hours, and 560 mL respectively. Keywords: Buleleng seawater, carbon electrodes, degrading leachate, electro-oxidation technique